Formation mechanism of continuous gas leakage paths in cement sheath during hydraulic fracturing. Issue 7 (20th March 2020) - Lian, Wei; Li, Jun; Tao, Qian; Du, Jinlong; Wang, Lei; Xi, Yan
Abstract: Continuous gas leakage paths of cement sheath during hydraulic fracturing were investigated in this study. The finite‐element models of a casing–cement‐sheath–formation assembly for the whole wellbore were established, the integrity of the cement sheath of the whole wellbore during single‐stage fracturing was analyzed firstly, and the factors affecting the integrity were examined. Furthermore, a cyclic compression test was conducted. Then, test results for the accumulative plastic strain of the cement sheath under the intermediate casing shoe during multistage fracturing were analyzed. Finally, the mechanism of dilatancy of cement stone in cyclic compression tests was analyzed. The results show that the radial and tangential stresses of the cement sheath increase and decrease, respectively, with depth. The cement sheath above the intermediate casing shoe had a risk of tensile failure, which could result in tangential tensile cracks. The cement sheath below the intermediate casing shoes had cumulative plastic strain, resulting in a microannulus. Reducing Young's modulus, increasing the Poisson ratio of the cement sheath, and reducing the pump pressure were beneficial to relieve the stress state. When the cyclic compressive stress exceeded the dilatation yield stress, the permeability increased with cycle numbers, and the increase in permeability provided another leakage path for gas migration. Abstract : This paper clarifies the sealing failure mode of cement sheath at different well depths during hydraulic fracturing. The cement sheath from the wellhead to intermediate casing shoe is tangential tensile failure. There are microannular gaps between cement sheath and casing under the intermediate casing shoe. When the cyclic compressive stress exceeds the dilatation yield stress, the permeability increases with the increase in cycle numbers, and the increase in permeability provided another leakage path for gas migration.